Differential Detection of Bioavailable Mercury and Cadmium Based on a Robust Dual-Sensing Bacterial Biosensor - Hui, Chang-ye; Guo, Yan; Li, Han; Chen, Yu-ting; Yi, Juan (Frontiers in Microbiology, 2022)
Genetically programmed biosensors have been widely used to monitor bioavailable heavy metal pollutions in terms of their toxicity to living organisms. Most bacterial biosensors were initially designed to detect specific heavy metals such as mercury and cadmium. However, most available biosensors failed to distinguish cadmium from various heavy metals, especially mercury. Integrating diverse sensing elements into a single genetic construct or a single host strain has been demonstrated to quantify several heavy metals simultaneously. In this study, a dual-sensing construct was assembled by employing mercury-responsive regulator (MerR) and cadmium-responsive regulator (CadR) as the separate sensory elements and enhanced fluorescent protein (eGFP) and mCherry red fluorescent protein (mCherry) as the separate reporters. Compared with two corresponding single-sensing bacterial sensors, the dual-sensing bacterial sensor emitted differential double-color fluorescence upon exposure to 0–40 μM toxic Hg(II) and red fluorescence upon exposure to toxic Cd(II) below 200 μM. Bioavailable Hg(II) could be quantitatively determined using double-color fluorescence within a narrow concentration range (0–5 μM). But bioavailable Cd(II) could be quantitatively measured using red fluorescence over a wide concentration range (0–200 μM). The dual-sensing biosensor was applied to detect bioavailable Hg(II) and Cd(II) simultaneously. Significant higher red fluorescence reflected the predominant pollution of Cd(II), and significant higher green fluorescence suggested the predominant pollution of Hg(II). Our findings show that the synergistic application of various sensory modules contributes to an efficient biological device that responds to concurrent heavy metal pollutants in the environment.